Saving Money at the Grocery Store - Glenda L. Warren (EDIS, 2009)
FCS-8851, a 2-page fact sheet by Glenda L. Warren, lists 21 strategies to save money on one’s grocery bill. Published by the UF Department of Family Youth and Community Sciences, December 2008. Reviewed with minor revision November 2011.